Physical properties and chemical composition of biofuels - Mohd Hafizil, Mat Yasin; Mohd Affandi, Ali; Rizalman, Mamat; Ahmad Fitri, Yusop; Mohd Hafiz, Ali (Elsevier, 2019)
Biofuels are considered as alternative fuels to the currently used fossil fuels. Their physical fuel characteristics and chemical composition are among the most important parameters to determine the quality of each fuel for use in engines. Strict procedures are used in observation and measurement according to the recommended standards, including American Society for Testing and Materials, to obtain the flash point, viscosity, density, acid value, and cetane number to define the actual properties of biofuels. These obtained properties are very beneficial for use in any arithmetical simulations for further findings. Also, these fuel properties provide good explanations on how the engine operates with those fuels regarding performance, combustion, and emission characteristics.